FUNGSI ELITIS PARPOL DALAM PEMBENTUKAN GOOD CITIZEN DAN GOOD GOVERNANCE - Muhammad Zimamul Wafi; Muhamad Khoerul Umam; M. Rafirsa Agung Pratama (Smart Education, 2025)
Abstract: People want justice and democracy is seen as the most likely way to achieve this. This assumption is based on the assumption that with democracy, the rights of the people as a whole will be fulfilled and with the distribution of people's aspirations, the needs of the community can be met. The existence of political parties as a place to accommodate the aspirations of the people will be increasingly important, where the functions of political parties if running certainly the dynamics of society will be democratic and lead to the formation of good governance and good citizens. Keyword: political parties; good citizenship; good governance. Abstrak: Rakyat menginginkan keadilan dan demokrasi dipandang sebagai suatu jalan yang paling mungkin mewujudkannya. Anggapan ini dari asumsi, bahwa dengan demokrasi, hak-hak rakyat dapat secara keseluruhan akan terpenuhi dan dengan didistribusikannya aspirasi rakyat maka kebutuhan masyarakat dapat terpenuhi. Keberadaan partai politik sebagai wadah menampung aspirasi makan akan semakin penting, dimana fungsi-fungsi partai politik apabila berjalan pastinya dinamika masyarakatnya akan demokratis dan mengarah pada terbentuknya good governance dan good citizen. Kata kunci: partai politik;good citizen;good governance.